Exploring the Root-Associated Bacterial Community of Tomato Plants in Response to Salt Stress - Antonia Esposito; Valeria Scala; Francesco Vitali; Marzia Beccaccioli; Massimo Reverberi; Giuseppe Valboa; Sara Del Duca; Loredana Canfora; Stefano Mocali (Agriculture)
Salinity is one of the main abiotic stresses that limits plant growth. This study addressed how the composition and diversity of root-associated bacterial communities reacts over time to salt-induced stress conditions. To understand its adaptation to soil salinization, the microbiome was studied by total DNA extraction and sequencing, using the Illumina MiSeq platform. Additionally, we evaluated the plant metabolites associated with salt stress (oxylipins, fatty acids (FAs) and hormones) by mass spectrometry. Salinity reduced rhizosphere bacterial diversity in salt-treated plants at 7 and 14 days and triggered a progressive shift of the bacterial structure, starting 7 days after salt stress imposed. The bacterial rhizosphere community became enriched with specific bacteria associated with potential genes involved in the PGP trait and ion homeostasis. For these plants, metabolites that showed higher levels included 9-lipoxygenase (LOX) oxylipins, which were found at days 7 and 14. The results indicated that salinity seems to have induced changes in the rhizosphere bacterial community, with characteristics that may help the plant respond to the imposed stress. Furthermore, our study highlighted the role of 9-LOX oxylipins in responding to salinity stress, providing new insights into the complex plant–microbe interactions under salt stress.